Pharmacological treatment of acute exacerbation of idiopathic pulmonary fibrosis: a retrospective study of 88 patients - Sakamoto, Susumu; Shimizu, Hirosige; Isshiki, Takuma; Kurosaki, Atsuko; Homma, Sakae (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Background: Acute exacerbation of idiopathic pulmonary fibrosis (AE-IPF) is often fatal. Although pharmacological treatments have been studied, outcomes remain poor. This study evaluated the effectiveness of pharmacological treatments for AE-IPF. Methods: This retrospective study comprised 88 patients who received a diagnosis of AE-IPF and were admitted to our center during the period from January 2008 through April 2017. We reviewed the clinical features, treatments, and outcomes of the 88 patients. Cox proportional hazards regression analysis was used to identify variables that were significant predictors of 3-month death. Results: Data from 88 AE-IPF patients (age range, 56-81 years) were analyzed. In all patients, corticosteroid (CS) pulse therapy was performed an average of 1.7 times, and the initial CS maintenance dose was 1 mg/kg for 65 patients and 0.5 mg/kg for 23 patients. The combination treatments received were sivelestat in 83 patients (94%), recombinant human thrombomodulin (rhTM) in 45 patients (51%), pirfenidone in 41 patients (47%), and cyclosporine in 71 patients (81%). Univariate analysis showed that use of rhTM, and an initial CS maintenance dose of 0.5 mg/kg were associated with better 3-month survival. In multivariate analysis, both use of rhTM and an initial CS maintenance dose of 0.5 mg/kg were associated with better 3-month survival. Other treatments, including sivelestat, cyclosporine, pirfenidone, and polymyxin B-immobilized fiber column-direct hemoperfusion, were not associated with better 3-month survival. Conclusion: Addition of rhTM to CS, and a low initial CS maintenance dose (0.5 mg/kg), were associated with better 3-month survival in patients with AE-IPF.